Proton therapy for pediatric and adolescent esthesioneuroblastoma. Issue 9 (27th March 2015) - Lucas, John T.; Ladra, Matthew M.; MacDonald, Shannon M.; Busse, Paul M.; Friedmann, Alison M.; Ebb, David H.; Marcus, Karen J.; Tarbell, Nancy J.; Yock, Torunn I.
<x xml:space="preserve">Abstract</x> Background Esthesioneuroblastoma (EN) of the paranasal sinus comprises less than 3% of tumors of in pediatric and adolescent patients [1]. The collective adult literature indicates a critical role for radiotherapy in attaining cure [2], yet pediatric outcome data is limited. Radiation in pediatric patients with EN can cause significant morbidity due to the proximity of critical structures. Proton radiotherapy offers a potential dosimetric benefit that may improve long‐term survival and toxicity outcomes in the pediatric population [3]. Methods We retrospectively identified eight patients treated for EN with proton radiotherapy from 2000‐2013. Times to event clinical endpoints are summarized using the Kaplan–Meier methods and are from the date of radiotherapy completion. Toxicities are reviewed and graded according to CTCAE v. 4.0. Results Median follow up was 4.6 years for survivors (range 0.8–9.4 years). The 4 year overall survival was 87.5%. Four of eight patients (one elective) had comprehensive neck radiotherapy. No local or regional failures were observed. Two patients failed distantly with diffuse leptomeningeal disease and intraparenchymal brain metastases, at 0.6 and 1.3 months respectively. Four patients developed radiation related late toxicities including endocrine dysfunction, two cases of grade 2 retinopathy and one case of grade 3 optic neuropathy. Conclusions In a limited cohort, proton radiotherapy appears to provide excellent locoregional disease control even in those patients with locally advanced disease and intracranial extension. Distant failure determined overall survival in our cohort. Toxicities were acceptable given disease location and extent. Pediatr Blood Cancer 2015;62:1523–1528. © 2015 Wiley Periodicals, Inc.